Character Education as Brain Education: Spiritual Neuroscience Studies in Islamic Education - Asman, Asman; Suyadi, Suyadi; Huda, Miftachul (Jurnal Tarbiyatuna, 2021)
Islamic education has been dogmatic because it emphasizes a behavioral approach, where the environment shapes the students' character. This contradicts neuroscience, where students have the potential to change their environment. Therefore, this literature study aimed to analyze character education as brain education from a neuroscience perspective using a qualitative approach. Data were then obtained manually and digitally from books and journals on neuroscience and Islamic education on the Sinta database and analyzed using content analysis. The results showed that character education using a behavioral approach does not produce students with good habits in the community. In contrast, the neuroscience approach allows them to develop a permanent good character identity with a transformative impact on the environment. These findings challenge a new direction of studies on Islamic education using a neuroscience approach with implications for shifting learning theory and practice.